Kultur pakan alami Alona sp. dalam media daun eceng gondok yang difermentasi dengan larutan Effective Microorganisme-4 - Sumah, Maria; Solang, Jhonly; Pangkey, Henneke; Mokolensang, Jeffrie F.; Lumenta, Cyska; Sinjal, Hengky Sinjal; Rumampuk, Natalie D. C. (Universitas Sam Ratulangi, 2021)
The purpose of this study was to examine the density of life feed Alona sp. on the media of water hyacinth leaf fermented with effective microorganism-4 (EM-4) solution. The method used was an experimental, using one-way ANOVA, with four treatments, namely fermented water hyacinth leaf media, unfermented water hyacinth leaf media, horse manure media, and water, each with three replications. The parameter observed was the density of Alona sp. The result showed that the density of Alona sp. cultured using fermented water hyacinth leaf media was significantly different from those cultured on unfermented water hyacinth leaf media.Â It had also been found that the density of Alona sp. high in horse manure media. However, it is recommended to use fermented water hyacinth leaf media, because it is more hygienic. In addition, the availability of horse manure is increasingly rare